2D Cu2−xSe@graphene multifunctional interlayer boosting polysulfide rapid conversion and uniform Li2S nucleation for high performance Li–S batteries. (1st April 2022) - Yuan, Meng; Shi, Haodong; Dong, Cong; Zheng, Shuanghao; Wang, Kai; Wang, Shaoxu; Wu, Zhong-Shuai
Abstract: Some vital challenges are main obstacles for further development of lithium–sulfur (Li–S) batteries such as low capacity and poor cycle stability resulted from polysulfide shuttling behavior, the physical/chemical entrapment is regarded as an effective method to inhibit and catalyze polysulfides. Herein we design a cross-linked framework of reduced graphene oxide anchored with Cu2− x Se nanoparticles (Cu2− x Se@rGO) by building an electrolyte/Cu2− x Se/graphene triple-phase interface to be a high-efficiency electrocatalyst for Li–S batteries. Importantly, this three-dimensional conductive network possesses a large specific surface area with high ion transport capability, meanwhile providing strong physical constraint for efficient adsorption of soluble polysulfides. Further, this triple-phase catalytic interface provides strong chemical adsorption and abundant Cu2− x Se nanoparticle sulfiphilic active sites, effectively inhibiting the dissolution of polysulfides and guaranteeing the efficient polysulfide adsorption catalysis as well as rapidly uniform Li2 S nucleation. Consequently, with the Cu2− x Se@rGO separator, a lower capacity decay rate about 0.059% per cycle after 500 cycles at 2 C is obtained. What's more, with a higher areal sulfur loading of 3.0 mg cm −2, the capacity is still maintained at 805 mAh g −1 over 100 cycles. Therefore, this work will open new avenue to construct 2D transition metal selenide for superior performance Li–S batteries.